Impact of Sexual Activity on Glycated Hemoglobin Levels in Patients with Type 2 Diabetes Mellitus after Penile Prosthesis Implantation - Talib, Raidh A.; Canguven, Onder; Al Ansari, Abdulla (Urology Journal, 2014)
Purpose: To examine the benefits of sexual activity on glycated hemoglobin (HbA1c)in penile prosthesis implanted patients with type 2 diabetes mellitus (DM). Materials and Methods: Sixty-seven male subjects who had HbA1c levels of ≥ 6.5% before and could perform regular sexual activity after the implantations were enrolled. The contribution of sexual activity on glycemic control assessed by HbA1clevel as well as age, duration of DM and frequency of sexual activity were evaluated. Results: Mean age and mean time from the surgery of the study patients was 59.9 years (range,30-82) and 22.6 months (range, 10-63), respectively. The average of penile prosthesis usage for sexual activity was 9.9 times per month (range, 2-28). Compared with the preimplantation, the absolute mean change in HbA1c after penile prosthesis implantation was found as - 0.2% (P > .05). This study also revealed that more sexual activity was associated with more reduction in HbA1c. Conclusion: The present study demonstrated that sexual activity is associated with HbA1c reduction, which is clinically important in patients with type 2 DM after penile prosthesis implantation.